Articulating Beliefs: A Comprehensive Analysis of English Teachers' Perspectives on Grammar Teaching - Wati, Siska Oktawidya; Syarif, Hermawati; Zainil, Yetti (Universitas Pahlawan Tuanku Tambusai, 2023)
Teacher beliefs are about how teachers conceptualize their work in classroom. Based on the theories, teacher beliefs is an important element in improving the quality of educational practice. Therefore, the purposes of this study are to describe the teachers‟ beliefs and to investigate how the teachers “practice of teaching grammar in classroom. The research method used is descriptive qualitative. The subjects of this study were two English teachers who were experienced in teaching English at SMPN 1 Harau. The instruments used are interview, field notes, and documents. The technique of data analyses used the Mile and Huberman model. Based on the result of the study the data show that teachers beliefs that grammar is important because it effects on how students make the correct sentence. There are five factors that support the beliefs, lesson plan, teaching method, teaching procedure, sources of teaching materials, the teachers and students roles. However, in teaching practices not those factors are applied because the teachers had to a lot of time to manage the classroom.